Viscosity Index Improvement of Lubricating Oil Fraction (SAE – 30) - Abdul-Karim Mohammed, Abdul-Halim; Shehab Al – Rubai, Amal Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
An investigation was conducted for the improvement of viscosity index of a lubricating oil fraction (SAE – 30) obtained from vacuum distillation unit of lube oil plant of Daura Refinery, using solvent extraction process. In this study two type of extraction solvents were used to extract the undesirable materials which reduce the viscosity index of raw lubricating oil fraction, the first solvent was furfural which is un use today in the Iraqi refineries and the second was NMP (N-methyl, 2, pyrrolidone) which is used for the first time in this work to extract the lubricating oil fraction produced from Iraqi crude oils. The studied effecting variables of extraction are extraction temperature range from 70 to 110 oC for furfural and NMP extraction, solvent to oil ratio range from 1:1 to 5:1 (wt/wt) for furfural extraction and from 0.5:1 to 2:1 (wt/wt) for NMP extraction. The results of this investigation show that the viscosity index of lubricating oil fraction increases with increasing extraction temperature and increasing the solvent to oil ratio and reaches 83 for NMP extraction at extraction temperature 110 oC and solvent to oil ratio 2:1, while the viscosity index reaches to 80 for furfural extraction at the same extraction temperature and solvent oil ratio. Higher viscosity index of lubricating oil fraction is obtained by using NMP instead of furfural under the same operating variables (extraction temperature and solvent to oil ratio). Further more, the results show that the viscosity, refractive index, and percentage yield of raffinate decreased as the extraction temperature or solvent to oil ratio increases for furfural and NMP extraction.